An Antithrombotic Strategy by Targeting Phospholipase D in Human Platelets - Lu, Wan Jung (J Clin Med, 2018)
Phospholipase D (PLD) is involved in many biological processes. PLD1 plays a crucial role in regulating the platelet activity of mice; however, the role of PLD in the platelet activation of humans remains unclear. Therefore, we investigated whether PLD is involved in the platelet activation of humans. Our data revealed that inhibition of PLD1 or PLD2 using pharmacological inhibitors effectively inhibits platelet aggregation in humans. However, previous studies have showed that PLD1 or PLD2 deletion did not affect mouse platelet aggregation in vitro, whereas only PLD1 deletion inhibited thrombus formation in vivo. Intriguingly, our data also showed that the pharmacological inhibition of PLD1 or PLD2 does not affect mouse platelet aggregation in vitro, whereas the inhibition of only PLD1 delayed thrombus formation in vivo. These findings indicate that PLD may play differential roles in humans and mice. In humans, PLD inhibition attenuates platelet activation, adhesion, spreading, and clot retraction. For the first time, we demonstrated that PLD1 and PLD2 are essential for platelet activation in humans, and PLD plays different roles in platelet function in humans and mice. Our findings also indicate that targeting PLD may provide a safe and alternative therapeutic approach for preventing thromboembolic disorders.